Military-Industrial and Military-Economic Dimensions of Sino-US Rivalry - V. B. Kashin (Сравнительная политика, 2021)
This article provides an assessment of the development of the military potential of China and the United States from the perspective of the growing confrontation between the parties. Special attention is paid to the development of innovations and to technological diplomacy. Due to the high level of innovations integration in the military and civil spheres, a military-technical competition initiates a full-scale confrontation in the economic and industrial spheres. The growing potential of China poses a challenge for the USA to constrain China’s technological development, including by limiting its possibilities for scientiﬁc and technological cooperation with other countries.